(3GdMjd aj GdMQhH haJM GdeOGFf hMaX GdOQhHs - (3GHf efcdj , eMeO Hf efcdj GdfGUQj,J (B770 (3g` s
(3ChdgG (B:s
(3hgPG cJGH GdMjd hef Mce Pi GdbQfjf GdCScfOQ GHf ajdHS GdjhfGfi s
(3BNQgG (B:s
(3Je cJGH GdMjd ai GdMQhH HYhf Gddg s
(3edc GdYHO GdabjQ Gdehdhi GdYdGFi YdGA GdOjf WjHZG GdYeQi GdSdais
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B112 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B8s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B136 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeI (B- (3U (B14 s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs